Soil organic carbon : Stratification and spatial variation of different fractions in an Argiudoll under no tillage - Salazar Landea, María Paz (2020)
Soil organic carbon (SOC) is an important factor for soil quality diagnosis. Physical and chemical fractionation of SOC are useful to characterize SOC, because some fractions are more sensitive indicators of the effects of different management practices. The aims of this study were (i) to determine values of SOC and different fractions of SOC at different depths and positions in an Argiudoll of the Argentinian Pampas under NT, and (ii) to determine the relation between physical and chemical fractions of SOC. In an experimental plot located in Chascomús, we determined SOC content, humic acids (HA), fulvic acids (FA), humins, coarse and fine particulate organic carbon (POCc and POCf) and mineral associated organic carbon (MOC), at different depths and in the row and inter-row. The content of SOC and different SOC fractions, as well as the contribution of each fraction to SOC showed a vertical variation. The contribution of HA and POCc (newer and more labile fractions) to SOC was larger in the surface than in deeper layers, while humins’ (older and more recalcitrant fraction) contribution to SOC increased with depth, and the contribution of FA, POCf and MOC to SOC remained relatively constant. There was no effect of row and inter-row in SOC content and composition. FA content was correlated to POCc, HA content to POCc and POCf and humins to MOC.